Genitourinary rhabdomyosarcoma in a child with urinary incontinence as the initial symptom: A case report and literature review - Jingde Wu; Rong Ma; Qingwei Zhang; Jianlin Xie; Xiande Huang (Urology Case Reports, 2025)
Rhabdomyosarcoma (RMS) is a morphologically heterogeneous high-grade malignancy that occurs uncommonly in the pediatric genitourinary (GU) system, and the most typical clinical symptoms are urinary frequency, urgency, hematuria, and associated with infection. The boys in this case, persistent urinary incontinence was relatively rare, and it was easily misdiagnosed as pediatric urinary incontinence in clinical diagnosis. Incontinence disease and lower urinary tract symptoms were identified by imaging examination, and final pathological biopsy confirmed the diagnosis of pediatric GU embryonal rhabdomyosarcoma (ERMS). Learning through case report and literature can help clinicians to better understand the manifestations and accurate diagnostic treatment of the disease.